Revolutionizing Healthcare Information Systems through Blockchain Technology - Srinivas Maddela, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Integrating blockchain technology in healthcare represents a transformative approach to addressing critical data security, interoperability, and patient privacy challenges. This comprehensive article examines the implementation of blockchain solutions across various healthcare domains, including clinical trials, pharmaceutical supply chains, and personalized medicine. The technology's distributed ledger architecture enables secure patient data sharing, enhances clinical trial management, and revolutionizes pharmaceutical supply chain oversight. Blockchain demonstrates significant potential in improving healthcare delivery efficiency through smart contracts and consensus mechanisms while maintaining regulatory compliance. The article explores the transformative benefits and implementation challenges, highlighting the technology's role in advancing patient-centric care and medical research while addressing concerns regarding scalability, system integration, and regulatory requirements.
Keywords: Blockchain Healthcare; Clinical Trial Management; ealthcare Data Security; Personalized Medicine; Pharmaceutical Supply Chain